The Influence of Marketing Communication on the Company Image of Marugame Udon Summarecon Mall Bekasi - Muhammad, Habibie; Sari, Sukarni Novita (Indonesian Scientific Publication, 2023)
One of the businesses that need a positive image through marketing communication is the food and beverage industry (restaurant), the development of restaurant business is seen from the increasing number of restaurants or restaurants, various types of food offered from traditional food, fast food, and food from abroad. This makes Marugame Udon to think how to maintain a positive image through proper marketing communication. This study aims to determine the effect of Marketing Communications on image. Population and sample of this study are consumers of Marugame Udon Summarecon Mall Bekasi. The method used is quantitative method. Data retrieval techniques are used in the form of questionnaires and literature. The population of this study was consumers of Marugame Udon. Sampling technique in this study is probability sampling with simple random sampling method. A sample of 100 samples. The data analysis used is multiple linear regression analysis using Statistical Packages for Social Science (SPSS). The results of this study showed that the variable marketing communication has a significant effect because the count 16.002 > ttable 1.984 with a significance level of 0.000 < 0.05. So it was concluded that there is a positive and significant influence between marketing communications to the image of Marugame Udon Summarecon Mall Bekasi amounted to 72.3%.